(untitled) (Crimson Journal of Science and Technology, 2025)
Clinical biochemistry is the foundation of modern healthcare, influencing almost every diagnostic and therapeutic decision made inside hospital systems. Despite global technical advancements, countries like as Nepal continue to face challenges in diagnostic access, quality control, automation, data integration, and expert workforce development. The COVID-19 pandemic has pushed the deployment of molecular platforms and point-of-care testing (POCT), but sustainability and standardization remain a challenge. This viewpoint examines persistent inadequacies in clinical biochemistry infrastructure and provides a realistic innovation roadmap for developing health systems. In contrast, new technological innovations—such as near-patient molecular diagnostics, biosensor-driven point-of-care platforms, advanced automated immunoassay systems, and AI-enabled quality assurance—open powerful possibilities for modernizing clinical biochemistry services. Achieving lasting progress, however, depends on investing in skilled human resources, reinforcing regulatory and accreditation mechanisms, promoting collaborative public–private models, and developing robust national reference laboratories to guide proficiency and standardization efforts. Strategic progress in clinical biochemistry has the potential to enhance diagnostic speed, improve disease detection, support rational antibiotic use, strengthen maternal care, and bolster national surveillance systems. For Nepal context, technological innovation must be accompanied by stronger quality systems, governance structures, and local production capacity. This paper calls for a phased, evidence-based modernization of laboratory services to ensure equitable and future-ready diagnostics.